2008
DOI: 10.1103/physreva.78.053606
|View full text |Cite
|
Sign up to set email alerts
|

Universal relations for a strongly interacting Fermi gas near a Feshbach resonance

Abstract: A set of universal relations between various properties of any few-body or many-body system consisting of fermions with two spin states and a large but finite scattering length have been derived by Shina Tan. We derive generalizations of the Tan relations for a two-channel model for fermions near a Feshbach resonance that includes a molecular state whose detuning energy controls the scattering length. We use quantum field theory methods, including renormalization and the operator product expansion, to derive t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
137
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 108 publications
(139 citation statements)
references
References 24 publications
2
137
0
Order By: Relevance
“…(b) Recently, the localization of minority atoms by an optical lattice was demonstrated with an imbalanced Bose-Bose mixture of 87 Rb and 41 K atoms [95]. The localization of the impurity atoms at length scales of roughly 10% of the Fermi wavelength has been achieved at typical densities; thus, the impurity can be treated as pointlike, and one can neglect its excitations to the excited states of the trapping potentials, as in our analysis above.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…(b) Recently, the localization of minority atoms by an optical lattice was demonstrated with an imbalanced Bose-Bose mixture of 87 Rb and 41 K atoms [95]. The localization of the impurity atoms at length scales of roughly 10% of the Fermi wavelength has been achieved at typical densities; thus, the impurity can be treated as pointlike, and one can neglect its excitations to the excited states of the trapping potentials, as in our analysis above.…”
Section: Discussionmentioning
confidence: 96%
“…This phenomenon, as well as the full structure of Að!Þ at k F jaj ) 1, can be understood as the result of a nontrivial interplay between two-body physics that involves the impurity and the hole near the bottom of the band, and the dynamics of multiple particle-hole excitations created at the Fermi surface. The possibility of a nontrivial interplay between many-body and few-body physics is a unique feature of ultracold-atom physics, and has attracted significant theoretical [86,87] and experimental [88] interest recently.…”
Section: Universal Radio-frequency Spectramentioning
confidence: 99%
“…The coefficient of the leading operator is a Dirac delta function of r ′ − r. It can be derived simply by using the (anti)commutation relations for the field operators. The coefficients of higher dimension operators can be calculated using diagrammatic methods [6,13]. Upon inserting the OPE in Eq.…”
Section: Operator Product Expansionmentioning
confidence: 99%
“…In particular, the HFT has recently been used to derive a number of exact relations for strongly-correlated systems with short-range interations, in the context of ultra-cold quantum gases [5,6,26]. Since this theorem applies only for pure states, these exact relations strictly hold at zero temperature for any change or equivalently at finite temperatures for an adiabatic change.…”
Section: A Hft For Pure Statesmentioning
confidence: 99%
“…It has been found that the contact parameter also appears in many other short-range (highmomentum) or short-time (high-frequency) properties of the system [11][12][13][14][15][16]. This parameter has recently been measured in an ultracold 40 K gas via the measurements of the highmomentum tail of the momentum distribution and of the highfrequency tail of the radio-frequency signal [17], and also measured in an ultracold 6 Li gas via the measurements of the static structure factor [18]. The measured temperature and scattering length dependence of the contact parameter compare well with the theoretical predictions [19,20].…”
Section: Introductionmentioning
confidence: 99%